Vitamin D deficiency in obese patients with Type 2 diabetes - Szafraniec, Aneta; Porada, Dominik; Matyjaszek-Matuszek, Beata (Journal of Education, Health and Sport, 2018)
Introduction: Vitamin D deficiency is involved in the pathogenesis of insulin resistance, which is the main factor in the development of type 2 diabetes. In Poland, a high percentage of people with vitamin D deficiency is observed, as well as incidences of type 2 diabetes. In 2013, recommendations regarding vitamin D supplementation for Central Europe inhabitants were published, which recommend the use of vitamin D preparations for obese people with a dose of 600-4000 IU / per Day Purpose of the work: Evaluation of the prevalence of vitamin D deficiency in obese patients with chronically decompensated type 2 diabetes mellitus and appropriate supplementation in accordance with given recommendations. Material and metod: Evaluation of laboratory tests and applied pharmacotherapy in 40 patients with chronically decompensated type 2 diabetes, aged from 38 to 89 years old. Results: In the experimental group the average concentration of 25 (OH) D3 was 20.3 ng / ml ± 11.7. Supplementation of vitamin D preparations was used by 15% of patients. Only 22.5% of patients had correct concentrations of 25 (OH) D3, but only one person used vitamin D supplements in this group. Conclusions: One in five obese patients with type 2 diabetes have normal levels of vitamin D. Among obese diabetics nearly 90% of patients do not apply the recommendations for vitamin D supplementation. Knowledge about the benefits of vitamin D supplementation should be widely propagated among diabetologists and general practitioners.